EFFECT OF ACID TYPE AND GELATION pH ON THE STRUCTURAL PROPERTIES OF SILICA AEROGELS PREPARED BY USE OF RICE HULL BIOSILICA - Karakuzu, Burcu; Temel, Tulay Merve; Yucel, Sevil; Terzioglu, Pinar; Elalmis, Yeliz (YILDIZ TECHNICAL UNIV, 2016)
In this study, the experimental results of the surface area, morphology, and density of silica aerogels obtained at different preparation conditions are reported. The aerogels have been produced by sol-gel process followed by ambient pressure drying. Rice hull ash silicate solution was used as an inexpensive precursor. The type of acids and gelation pH has strongly affected the structural properties of the final products. The silica aerogels have a well-developed nanoporous structure and a high specific surface area. The densities, pore sizes and specific surface areas of the silica aerogels were in the range of 0.273-0.849 g cm(-3), 3.24-10.22 nm, and 238-726 m(2)g(-1), respectively.
Keywords: Ambient pressure drying; rice hull; silica aerogel; ASH; Engineering